Will the white blood cells tell? A potential novel tool to assess broiler chicken welfare - Ribeiro, Laura Raquel Rios; Sans, Elaine Cristina de Oliveira; Santos, Ricardo Martins; Taconelli, Cesar Augusto; de Farias, Roberta; Molento, Carla Forte Maiolino (Frontiers in Veterinary Science, 2024)
This study assessed qualitative and quantitative leukocyte evaluation as potential broiler chicken welfare indicators, contributing to the limited literature on white blood cell (WBC) morphology as a diagnostic tool for welfare. Broiler chicken welfare within four poultry houses (PH) 1 to 4, each on a different farm, was assessed using on-field indicators of affective states and health, and WBC morphology was examined. Affective states were evaluated using the Qualitative Behavior Assessment (QBA), with 25 behavioral expressions scored on a visual analogue scale (VAS) and grouped into two categories. Health indicators included assessments of lameness, footpad dermatitis, dermatitis on the breast and abdominal areas, hock burn, and feather cleaning. Blood samples were collected, differential leukocyte counts were performed, and a cell score was created for the recognition, classification, and interpretation of morphologic diversity of heterophils and lymphocytes. The heterophil to lymphocyte ratio (H/L) was also determined. Descriptive statistics and generalized linear models for binomial responses were used to analyze the results. PH4 differed from the other farms, showing a higher frequency of birds within QBA group 1 (‘Attentive’to ‘Desperate’), while birds in PH1, PH2, and PH3 were more frequent in QBA group 2 (‘Relaxed’ to ‘Positively occupied’). Elevated proportions of heterophils in birds from PH4 (0.61, CI95%: 0.58; 0.64) and PH3 (0.60, CI95%: 0.57; 0.63) suggested higher stress levels and inflammatory responses. Birds in PH2 and PH4 exhibited higher frequencies of health issues such as dermatitis and lameness, and higher proportions of abnormalities in WBC number and morphology. PH3 and PH4 exhibited higher H/L ratios of 3.03 and 2.58, respectively, consistent with the on-field health and behavioral indicators. Blood samples from birds in PH2 and PH4 showed a proportion of 90% toxic change in heterophils, while in PH1 and PH3 it was 70%, indicating high levels of abnormal WBC morphology across all PHs. The findings emphasize the multifactorial nature of welfare impairments, including environmental conditions, health, and affective states. This highlights the need for indicators that reflect multiple welfare impacts, such as WBC counts and morphological alterations, which can serve as powerful tools in the complex task of assessing animal welfare.